LOW-COST METHODOLOGY FOR THE FOLLOW-UP AND MONITORING OF MUSCLE RECOVERY, BASED ON VIDEO GAME TECHNIQUES, APPLIED TO CHILDREN, IN TIMES OF PANDEMIC CAUSED BY COVID-19 - Wilver AUCCAHUASI, Sandra MEZA, Kitty URBANO, William HEREDIA (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
At present, information and communication technologies are achieving notable importance in all actions of people, from education, work and with greater emphasis on health. It is in this area of knowledge that many applications arise based on the use of hardware and software that try to help medical diagnosis, in this work we use the video game console "Nintendo Switch" to interact with the child, so that children They can play the games and at the same time be able to perform the rehabilitation exercises, depending on the muscles to be recovered, in our case it is evaluated to recover the mobility of the "elbow" and the muscles that interact with it, in a normal situation, children have complications in performing rehabilitation exercises in health centers, this refusal to perform the exercises may be due to fear or even more so, the environment itself does not allow them to feel confident. The results allowed us to show that children can perform rehabilitation exercises at home using the Nintendo Switch console, for the verification of the methodology, it was possible to configure the console with wireless controls so that children can interact with the game "Just Dance" , where children try to perform the same movements that are presented in the video game, with the help of the surface electromyography circuit, the muscle activity linked to the signals can be recorded. We can indicate that the methodology presented allows the use of a device that children feel more comfortable and identified for complex tasks such as the issue of recovery of elbow mobility, it can also be possible to record each movement with its respective muscle activity, for analysis later by the doctor of the specialty of Physical Therapy and rehabilitation.